Fucoidan Ameliorates Renal Injury-Related Calcium-Phosphorus Metabolic Disorder and Bone Abnormality in the CKD–MBD Model Rats by Targeting FGF23-Klotho Signaling Axis - Liu, Bu-Hui; Chong, Fee-Lan; Yuan, Can-Can; Liu, Ying-Lu; Yang, Hai-Ming; Wang, Wen-Wen; Fang, Qi-Jun; Wu, Wei; Wang, Mei-Zi; Tu, Yue; Wan, Zi-Yue; Wan, Yi-Gang; et al. (Frontiers in Pharmacology, 2021)
Background: Recently, chronic kidney disease (CKD)-mineral and bone disorder (MBD) has become one of common complications occurring in CKD patients. Therefore, development of a new treatment for CKD–MBD is very important in the clinic. In China, Fucoidan (FPS), a natural compound of Laminaria japonica has been frequently used to improve renal dysfunction in CKD. However, it remains elusive whether FPS can ameliorate CKD–MBD. FGF23-Klotho signaling axis is reported to be useful for regulating mineral and bone metabolic disorder in CKD–MBD. This study thereby aimed to clarify therapeutic effects of FPS in the CKD–MBD model rats and its underlying mechanisms in vivo and in vitro, compared to Calcitriol (CTR). Methods: All male rats were divided into four groups: Sham, CKD–MBD, FPS and CTR. The CKD–MBD rat models were induced by adenine administration and uninephrectomy, and received either FPS or CTR or vehicle after induction of renal injury for 21 days. The changes in parameters related to renal dysfunction and renal tubulointerstitial damage, calcium-phosphorus metabolic disorder and bone lesion were analyzed, respectively. Furthermore, at sacrifice, the kidneys and bone were isolated for histomorphometry, immunohistochemistry and Western blot. In vitro, the murine NRK-52E cells were used to investigate regulative actions of FPS or CTR on FGF23-Klotho signaling axis, ERK1/2-SGK1-NHERF-1-NaPi-2a pathway and Klotho deficiency. Results: Using the modified CKD–MBD rat model and the cultured NRK-52E cells, we indicated that FPS and CTR alleviated renal dysfunction and renal tubulointerstitial damage, improved calcium-phosphorus metabolic disorder and bone lesion, and regulated FGF23-Klotho signaling axis and ERK1/2-SGK1-NHERF-1-NaPi-2a pathway in the kidney. In addition, using the shRNA-Klotho plasmid-transfected cells, we also detected, FPS accurately activated ERK1/2-SGK1-NHERF-1-NaPi-2a pathway through Klotho loss reversal. Conclusion: In this study, we emphatically demonstrated that FPS, a natural anti-renal dysfunction drug, similar to CTR, improves renal injury-related calcium-phosphorus metabolic disorder and bone abnormality in the CKD–MBD model rats. More importantly, we firstly found that beneficial effects in vivo and in vitro of FPS on phosphorus reabsorption are closely associated with regulation of FGF23-Klotho signaling axis and ERK1/2-SGK1-NHERF-1-NaPi-2a pathway in the kidney. This study provided pharmacological evidences that FPS directly contributes to the treatment of CKD–MBD.